2016
DOI: 10.3390/en9100765
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Travel Behaviors and Transport Carbon Emissions: A Comparative Study of Commercial Centers in Shenyang, China

Abstract: Current literature highlights the role of commercial centers in cities in generating shopping trips and transport carbon emissions. However, the influence of the characteristics of commercial centers on consumer travel behavior and transport carbon emissions is not well understood. This study addresses this knowledge gap by examining shopping trips to eight commercial centers in Shenyang, China, and the CO 2 emissions of these trips. We found that the locations and types of commercial centers strongly influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Commercial services have been greatly improved, with retail sales of consumer goods reaching 363.61 billion RMB in 2015. Eight typical commercial centers were selected as our field sites based on their location characteristics and types of retail present [ 57 ]. Middle Street and Taiyuan Street are two municipal commercial centers at the city center, with a large business circle covering the entire municipality of Shenyang, and even extending to surrounding cities.…”
Section: Methodsmentioning
confidence: 99%
“…Commercial services have been greatly improved, with retail sales of consumer goods reaching 363.61 billion RMB in 2015. Eight typical commercial centers were selected as our field sites based on their location characteristics and types of retail present [ 57 ]. Middle Street and Taiyuan Street are two municipal commercial centers at the city center, with a large business circle covering the entire municipality of Shenyang, and even extending to surrounding cities.…”
Section: Methodsmentioning
confidence: 99%
“…They further established that innovation and infrastructure development with an increased absorptive capacity could help lessen the carbon intensity of China and the US. Li et al [26] found that the average CO 2 emissions of suburban commercial centers were 6.94% and 26.92%, which are higher than those of urban commercial centers. The CO 2 emissions of wholesale centers were nearly three times less than those of the inner-city commercial centers.…”
Section: Impact Of Transport Energymentioning
confidence: 99%
“…where i represents the travel mode; ECO 2 is the estimated CO 2 emissions (g); F i is the average fuel consumption rate of the travel mode i (m 3 /100 km or L/100 km); ρ is the fuel density (kg/m 3 ); D is the travel distance (km); EF is the carbon emissions factor of fuel (t CO 2 /1000 Nm 3 or t CO 2 /t) and AC is the estimated transport capacity (Li et al, 2016). Carbon emissions for rail transit are demonstrated as follows:…”
Section: Model 231 Co 2 Emissions Modelmentioning
confidence: 99%
“…where p represents the travel mode; ECO 2 is the estimated CO 2 emissions (g); C is the average power consumption (kWh/100 km); D is the travel distance (km); EF is the carbon emissions factor of power (kg/kWh) and AC is the estimated transport capacity (Li et al, 2016).…”
Section: Model 231 Co 2 Emissions Modelmentioning
confidence: 99%
See 1 more Smart Citation